Efficacy of pulsed radiofrequency stimulation in patients with chronic pain: a narrative review - Lin, Wei; Lou, Lingling; Chu, Dawei; Lv, Yidong; Tian, Liujun; Wang, Bin (Frontiers in Pain Research, 2025)
ObjectivesThe review aimed to evaluate the efficacy of pulsed radiofrequency (PRF) in treating chronic pain by analyzing recent literature.Study designThis is a narrative review of relevant articles on the effectiveness of PRF for chronic pain.MethodsSearch for papers published between November 2014 and November 2024 in the PubMed database that use PRF to treat chronic pain. We used “Pulsed radiofrequency, PRF, Pulsed RF for Pain, chronic pain, neuropathic pain, cancer pain, and osteoarthritis pain” as search terms. Inclusion criteria are as follows: (1) Patients are clearly diagnosed with chronic pain according to the standards of the International Association for the Study of Pain; (2) Pulsed radiofrequency is used to treat chronic pain; (3) Follow-up assessments are conducted to evaluate the degree of pain relief after PRF treatment; (4) Review articles and articles not related to the treatment of chronic pain are excluded.ResultsPreliminary searches yielded 368 relevant articles. After reviewing the titles and abstracts and evaluating the full texts, we ultimately included 80 articles. These articles cover research on pulsed radiofrequency treatment for various chronic pain conditions, including neuropathic pain, osteoarthritis pain, and cancer pain. The study types are diverse, including randomized controlled trials, cohort studies, and case reports. The publication dates of the articles range from 2014 to 2024, ensuring the timeliness and comprehensiveness of the research findings, which reflect the latest advancements and outcomes in the field of pulsed radiofrequency treatment for chronic pain.LimitationsThis review did not include studies indexed in databases other than PubMed.ConclusionThis article reviews the research progress of pulsed radiofrequency technology in the field of chronic pain treatment. By searching and analyzing relevant literature from recent years, it summarizes the research findings on the mechanisms of PRF in treating chronic pain, its clinical applications, efficacy evaluation, and safety, and discusses future research directions. This is helpful for clinical physicians to develop more scientific treatment plans when managing chronic pain patients.